2023
DOI: 10.3390/molecules28041770
|View full text |Cite
|
Sign up to set email alerts
|

The Epigenetic Effects of Coffee

Abstract: In this review, we discuss the recent knowledge regarding the epigenetic effects of coffee extract and the three essential active ingredients in coffee (caffeine, chlorogenic acid, and caffeic acid). As a popular beverage, coffee has many active ingredients which have a variety of biological functions such as insulin sensitization, improvement of sugar metabolism, antidiabetic properties, and liver protection. However, recent researches have shown that coffee is not only beneficial for human, but also bad, whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 78 publications
0
2
0
Order By: Relevance
“…When possible, the review listed mechanisms that might explain the relationship of disease comorbidities to AD. Another recent review outlined the health benefits of Coffee Caffeic acid is one of three active ingredients in coffee [226].…”
Section: Discussionmentioning
confidence: 99%
“…When possible, the review listed mechanisms that might explain the relationship of disease comorbidities to AD. Another recent review outlined the health benefits of Coffee Caffeic acid is one of three active ingredients in coffee [226].…”
Section: Discussionmentioning
confidence: 99%
“…Hernandes et al [ 166 ] revealed that CGA restored the CpG hypomethylation status of cancer and then predisposed the cancer cells to its cytotoxic and genotoxic effects [ 166 ]. Ding et al [ 167 ] asserted that CGA modulates gene expression patterns by restoring normal epigenetic signatures such as CpG island DNA methylation, histone post-translational modification, and microRNA expression [ 167 ]. In their investigation of the roles of CGA on epigenetic reprogramming in breast cancer, Lee and Zhu [ 112 ] found that CGA inhibits DNA methyltransferase (DNMT) to prevent hypermethylation of the DNA sequence in both triple negative and triple positive breast cancer cells [ 112 ].…”
Section: Chlorogenic Acid and Cinnamaldehydementioning
confidence: 99%
“…Coffee can impact gene expression via alteration of DNA methylation, histone modificationes and ncRNA expression. Understanding the epigenetic effects is important to finding ways for improving human health (Ding et al 2023).…”
Section: Figure 1 the Repartion Of The Cases According To The Caffee ...mentioning
confidence: 99%